Using modified Alvarado score in conservative treatment of acute appendicitis - Baderkhan Saeed Ahmed (Advanced Medical Journal)
Background and objectives: Acute appendicitis is the most common and challenging surgical emergencies. The diagnosis is still based on the clinical examination. The modified alvarado score system isa safe diagnostic modality without extra expense and complications. Efficacy ofantibiotic treatment was often considered as a bridge to surgery inselectedpatients with acute appendicitis aided by using of Modified Alvarado scoring system.